Current scenario of autism spectrum disorders (ASDs) in Malaysia - Ong, Sing Yee; Roslan, Samsilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This is an overview of the current situation on Autism Spectrum Disorders (ASDs) in Malaysia. Recently ASDs has been the limelight in Malaysia. Anyhow, the exact statistics indicating of ASDs among children is not clearly stated. Even though there are treatment and assistance towards children with ASDs, unfortunately, the public only have limited resources towards these services in government department and private institutions. Research has been carried out towards ASDs. There were 18 articles that discussed about ASDs in Malaysia which gave focus in education, parents, intervention, social skills and general issues on ASDs.